2014
DOI: 10.15376/biores.9.4.7494-7503
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Sanding Parameters, Sanding Force, Normal Force, Power Consumption, and Surface Roughness in Sanding Wood-Based Panels

Abstract: The proper parameters of sanding with an abrasive sanding machine are significant to reduce energy consumption and to improve processing efficiency and quality. The influences of grit size (G), feed speed (U), sanding speed (V), and sanding thickness (Ts) on the sanding force (sF), normal force (nF), arithmetic mean deviation of profile (Ra), power consumption (P), and power efficiency (ε) were analyzed by the orthogonal method in this study. Fuzzy synthetic evaluation (FSE) was adopted to evaluate sF, P, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 5 publications
0
8
0
Order By: Relevance
“…In this example, PETG-0, PETG-0.5, and PETG-2 refer to polyethylene terephthalate glycol composite with 0 %, 0.5 %, and 2 % by mass fraction of multiwall carbon nanotubes, respectively. Consider the two use scenarios where abrasion of a similar plastic product occurs by sanding (ranges from 1 J/s to 300 J/s based on sander used) or chewing (average male jaw around 61 J/s) [8][9][10][11]. Abrasion rate of PETG-2 can be calculated for a specific power input (e.g., 1 J/s) value simply by multiplying the slope of the fitted line (0.3064 from Figure 3) by the power input to obtain a value for abrasion rate of 0.31 g/m 2 /s [9].…”
Section: Extrapolating Lab Results To Human or Environmental Implicationmentioning
confidence: 99%
“…In this example, PETG-0, PETG-0.5, and PETG-2 refer to polyethylene terephthalate glycol composite with 0 %, 0.5 %, and 2 % by mass fraction of multiwall carbon nanotubes, respectively. Consider the two use scenarios where abrasion of a similar plastic product occurs by sanding (ranges from 1 J/s to 300 J/s based on sander used) or chewing (average male jaw around 61 J/s) [8][9][10][11]. Abrasion rate of PETG-2 can be calculated for a specific power input (e.g., 1 J/s) value simply by multiplying the slope of the fitted line (0.3064 from Figure 3) by the power input to obtain a value for abrasion rate of 0.31 g/m 2 /s [9].…”
Section: Extrapolating Lab Results To Human or Environmental Implicationmentioning
confidence: 99%
“…47 In this manner, values of abrasion during sanding are calculated to range from 0.28 to 83 g/m 2 /s, 0.30 to 90 g/m 2 /s, and 0.31 to 92 g/m 2 /s for PETG-0, PETG-0.5, and PETG-2, respectively. 46,47 For chewing, an estimation of the power input is calculated assuming a mean molar force for males of 383.9 N based on an average male jaw length of 118.5 mm 48,49 and an instantaneous chew time of 0.75 s to obtain a estimated power of 61 J/s. Composite abrasion is then calculated as 0.3064 × 61 = 19 g/m 2 /s.…”
Section: Resultsmentioning
confidence: 99%
“…For example, consider the two use scenarios where abrasion of a similar plastic product ocurrs by sanding (ranges from 1 to 300 J/s based on sander used) or chewing (average male jaw around 61 J/s). For example, using a power input of sanding of 1 J/s for the PETG-2% composite, the abrasion rate is calculated by multiplying the slope (Figure ) by the power input, 0.3064 × 1, to obtain a value for the abrasion rate of 0.31 g/m 2 /s . In this manner, values of abrasion during sanding are calculated to range from 0.28 to 83 g/m 2 /s, 0.30 to 90 g/m 2 /s, and 0.31 to 92 g/m 2 /s for PETG-0, PETG-0.5, and PETG-2, respectively. , For chewing, an estimation of the power input is calculated assuming a mean molar force for males of 383.9 N based on an average male jaw length of 118.5 mm , and an instantaneous chew time of 0.75 s to obtain a estimated power of 61 J/s. Composite abrasion is then calculated as 0.3064 × 61 = 19 g/m 2 /s.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, different researchers have indicated that tangential cutting results in a softer surface than radial cutting, but the interaction among the cutting destination and sort of cutter is not significant (Örs and Baykan 1999;Örs and Gürleyen 2002;Efe and Gürleyen 2003;Söğütlü 2005;Malkoçoğlu 2007). Studies in which the Ra was optimized with an experimental design method (response surface design) have frequently been conducted in recent years and mostly in different areas (Kant and Sangwan 2014;Luo et al 2014;López et al 2016;Nguyen and Hsu 2016;Sofuoglu 2017).…”
Section: Introductionmentioning
confidence: 99%